Training of personnel for the development of domestic tourism in the Krasnodar Territory as a factor of socio-economic development of the region - O. V. Shpyrnya (Вестник Майкопского государственного технологического университета, 2024)
One of the main regional drivers for the development of domestic tourism in our country is the Krasnodar Territory. Taking into account the strategic development of the industry until 2030, there is a significant shortage of personnel for the effective development of domestic tourism in the Krasnodar Territory. As a result, it is possible to formulate a research problem caused by a significant gap between the requirements of the socio-economic development of the region and the current state of affairs in the field of personnel training for the development of domestic tourism in the Krasnodar Territory.The goal of the research is to identify the main problems in the process of training personnel for the development of domestic tourism in the Krasnodar Territory, and to formulate the main directions for optimizing this process. The methodological basis of the research is determined by the use of such scientific research methods as studying scientific literature, analysis, generalization, description.The research results: it has been determined that currently the personnel shortage in the domestic tourism industry, according to various estimates, ranges from 30% to 40%. At the same time, there are a number of significant problems in the system of training personnel for the development of domestic tourism in the Krasnodar Territory as a factor in the socio-economic development of the region. Accordingly, it is necessary to correct the personnel training process for the development of domestic tourism in the Krasnodar Territory.Key conclusions: It is necessary to revise training curricula towards their practice-oriented nature, taking into account the development of digital technologies, improve career guidance work, and more actively involve employer representatives in the development of curricula, as well as current and intermediate certification.